1999
DOI: 10.1007/s004050050129
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and morphometric investigations of the influence of botulinum toxin on the submandibular gland of the rat

Abstract: Immunohistochemical methods were used to study the effects of botulinum toxin A on the concentration of acetylcholinesterase in the submandibular gland of the rat. The toxin was injected into the glands of healthy adult female Wistar rats and immunohistochemistry performed on the excised organs. Morphometric measurements were also carried out to study changes of cell morphology after local applications of botulinum toxin A. Compared with untreated glands or glands injected with saline there was a decrease of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 16 publications
0
32
0
6
Order By: Relevance
“…Thus, it is clear that the results found by Teymoortash et al (2007), are different from those found by Ellies et al (1999), since these last authors claim to be no clear difference between the serous acini of treated and untreated groups. Teymoortash et al (2007), affirm that in the first study performed by Ellies et al (1999), morphometric evaluations were limited to the description of serous acinar cell nuclei and did not use a standard method of fixation to minimize differences in shrinkage of the tissue samples.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Thus, it is clear that the results found by Teymoortash et al (2007), are different from those found by Ellies et al (1999), since these last authors claim to be no clear difference between the serous acini of treated and untreated groups. Teymoortash et al (2007), affirm that in the first study performed by Ellies et al (1999), morphometric evaluations were limited to the description of serous acinar cell nuclei and did not use a standard method of fixation to minimize differences in shrinkage of the tissue samples.…”
Section: Discussionmentioning
confidence: 73%
“…The use of the toxin in sialorrhea treatment was based on a publication in 1923, when Dickson and Shevsky observed that the tympanic nerve, which induces salivation, was blocked in cats infected by Clostridium botulinum (Savarese et al, 2004;Ellies et al, 1999). As a therapeutic resource, the toxin was released to patient administration just in 1989, when the FDA (Food and Drugs Administration) classified it as safe and effective drug for the treatment of movement disorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations